Formation of the Zengmu and Beikang Basins, and West Baram Line in the southwestern South China Sea margin - Han, Bing; Zhao, Zhongxian; Wang, Xiaofang; Sun, Zhen; Li, Fucheng; Zhu, Benduo; Yao, Yongjian; Liu, Liqiang; Peng, Tianyue; Long, Genyuan (Journal of oceanology and limnology, 2023)
The Zengmu and Beikang Basins, separated by the West Baram Line (WBL) in the southwestern South China Sea margin, display distinct geological and geophysical features. However, the nature of the basins and the WBL are debated. Here we explore this issue by conducting the stratigraphic and structural interpretation, faults and subsidence analysis, and lithospheric finite extension modelling using seismic data. Results show that the WBL is a trans-extensional fault zone comprising normal faults and flower structures mainly active in the Late Eocene to Early Miocene. The Zengmu Basin, to the southwest of the WBL, shows an overall synformal geometry, thick folded strata in the Late Eocene to Late Miocene (40.4–5.2 Ma), and pretty small normal faults at the basin edge, which imply that the Zengmu Basin is a foreland basin under the Luconia and Borneo collision in the Sarawak since the Eocene. Furthermore, the basin exhibits two stages of subsidence (fast in 40.4–30 Ma and slow in 30–0 Ma); but the amount of observed subsidence and heat flow are both greater than that predicted by crustal thinning. The Beikang Basin, to the NE of the WBL, consists of the syn-rift faulted sub-basins (45–16.4 Ma) and the post-rift less deformed sequences (16.4–0 Ma). The heat flow (∼60 mW/m 2 ) is also consistent with that predicted based on crustal thinning, inferring that it is a rifted basin. However, the basin shows three stages of subsidence (fast in 45–30 Ma, uplift in 30–16.4 Ma, and fast in 16.4–0 Ma). In the uplift stage, the strata were partly folded in the Late Oligocene and partly eroded in the Early Miocene, which is probably caused by the flexural bulging in response to the paleo-South China Sea subduction and the subsequent Dangerous Grounds and Borneo collision in the Sabah to the east of the WBL.